Drug Delivery Options for Riluzole in the Treatment of Amyotrophic Lateral Sclerosis - Jaber Aghajani; Yousef Deljavan; Maryam Haghighatdoust (Neurology Letters)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by the selective degeneration of motor neurons, leading to muscle atrophy, paralysis, and eventual death. Despite extensive research, treatment options remain limited, with riluzole being the first and one of the few FDA-approved drugs for ALS. Riluzole acts by inhibiting glutamatergic neurotransmission and may provide a modest increase in survival and slower progression of symptoms. However, its clinical efficacy is significantly hindered by poor bioavailability, rapid metabolism, and challenges in delivering therapeutic concentrations to the central nervous system (CNS). These limitations stem from the blood-brain barrier (BBB), systemic side effects, and patient compliance issues. This review evaluates current and emerging strategies for improving riluzole delivery in ALS treatment. The review discusses conventional methods, such as oral and intravenous delivery, highlighting their limitations. It then explores advanced drug delivery approaches, including nanoparticles, liposomes, micelles, and transdermal systems, which offer promising alternatives for overcoming riluzole's pharmacokinetic barriers. Preclinical and clinical evidence is critically assessed to determine the efficacy and safety of these innovative systems. Additionally, emerging technologies such as gene therapy, hydrogel-based systems, and nanotechnology-enabled delivery mechanisms are analyzed for their translational potential. The findings underscore the need for interdisciplinary research to optimize riluzole delivery systems and improve ALS management.This paper aims to provide a comprehensive overview of the current landscape and highlight areas for future exploration.